Znaczenie leksemu bezecny i jego funkcja w Zwierciadle saskim Pawła Szczerbica - Jurewicz-Nowak, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The purpose of the article was to conduct a semantic and functional analysis of the lexeme infamous based on the material from Zwierciadło saskie (Saxon mirror) by Paweł Szczerbic. Infamous is a hyperonym for names defining an entity which does not respect the values that are the foundation of law, and which violates ethical and moral principles. This is a concept defined in the relic. The lexeme appears in a nominal function, in the specialized meaning of ‘condemned by law to loss of honour’. In certain contexts, its meaning becomes more specific. The sender’s desire for terminological precision is manifested both at the level of the text’s structure style (avoiding synonyms, derivative words). Calling someone infamous in the formula of presenting an accusation was a performative act of slander and accusation which caused specific legal consequences.